Ragel Alfan’s Niskala Seblang Choreography in Banyuwangi - Wiranto, Ari; rahayu, eko wahyuni (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
This research aims to describe the form of choreography by Ragel Alfan from Banyuwangi. Niskala Seblang is a form of group choreography that raises the theme of rituals based on the Osing Banyuwangi ethnicity. The research was conducted using qualitative research methods and data collection techniques include: literature study, observation, interviews and documentation. Data validity was tested using triangulation (source triangulation, method triangulation, and time triangulation). Data analysis is done through data reduction, data presentation and conclusion drawing. In discussing the problems in this study using the approach of the concept of choreography by Sal Murgiyanto and the concept of dance form revealed by Soedarsono. The results of the study show: (1) Nsiakala Seblang as a form of group dance choreography that elevates the life of the Seblang ritual tradition in Olehsari Village, Glagah District, Banyuwangi Regency. Niskala Seblang is choreographed beautifully through a combination of supporting elements of the dance form including: movement patterns and techniques, dance music, make-up design, and dance property, all of which produce a distinctive dance style and character, and express the cultural values of the Banyuwangi region with the characteristics of the Osing tribe. Keywords: Choreography, Niskala Seblang, Ragel Alfan.